2020
DOI: 10.1097/anc.0000000000000703
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Experiences About Support Following Stillbirth and Neonatal Death

Abstract: Background: Stillbirth and neonatal death are one of the most stressful life events, with negative outcomes for parents. Society does not recognize this type of loss, and parental grieving is particularly complicated and intense. Purpose: The aim of this study was to describe and understand the experiences of parents in relation to professional and social support following stillbirth and neonatal death. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 39 publications
2
56
0
Order By: Relevance
“…Numerous factors contribute to increase the risk of complicated grief in perinatal loss, such as the unexpected and sudden circumstances of the perinatal death, the lack of memories of the baby’s existence, and the self-blame for the pregnancy loss (Camacho-Ávila et al, 2020). In a descriptive cross-sectional, correctional study in Spain by Druguet et al (2018), the researchers concluded that intensity of grief was not determined by the period of the pregnancy at which the loss occurred, previous miscarriages, the presence of living children, the survival of one of the twins, or any of the sociodemographic variables examined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous factors contribute to increase the risk of complicated grief in perinatal loss, such as the unexpected and sudden circumstances of the perinatal death, the lack of memories of the baby’s existence, and the self-blame for the pregnancy loss (Camacho-Ávila et al, 2020). In a descriptive cross-sectional, correctional study in Spain by Druguet et al (2018), the researchers concluded that intensity of grief was not determined by the period of the pregnancy at which the loss occurred, previous miscarriages, the presence of living children, the survival of one of the twins, or any of the sociodemographic variables examined.…”
Section: Resultsmentioning
confidence: 99%
“…The phenomenological qualitative study carried out by Meaney, Corcoran, Spillane, et al (2017) about the experience of miscarriage indicates that this experience has a considerable impact on men and women, and the participants stated that it was important the acknowledgment of the loss by health professionals and more broadly throughout society. However, perinatal or neonatal losses are not socially recognized or viewed as a significant problem, for this reason, the grieving may not be recognized openly, there may not be public grief or be socially accepted (Al-Maharma et al, 2016; Camacho-Ávila et al, 2020). As shown in one qualitative study based on the Gadamer’s hermeneutic phenomenology (Camacho-Ávila et al, 2020), the feeling of biological failure and shame experienced by the mothers made them feel socially stigmatized and avoid contact with other people in their surroundings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Worden included such environmental factors as "mediator 6: social variables" [36]. Although the individual implications of perinatal death on the parents [11][12][13][14][15][16][17][18] and the social support available to survivors [37] have been extensively investigated, there is a lack of research involving fathers [38,39]. Moreover, the impact of PD on the social environment and the extended family has been poorly investigated [40].…”
Section: Introductionmentioning
confidence: 99%